Author Correction: Epitope-directed monoclonal antibody production using a mixed antigen cocktail facilitates antibody characterization and validation (vol 6, 441, 2021) - Liew, Oi Wah (NATURE RESEARCH, 2021)
10.1038/s42003-021-02091-4